A study of the dynamics of quantum correlations - Camati, Patrice Audibert [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work, we present an introduction to the quantum information theory. Before dealing with quantum information we develop some necessary tools, the classical information theory and some important concepts in quantum dynamics. We de?ne measures of quantum correlations, concurrence and quantum discord, and study their dynamical evolution when the coupling between the system and environment is considered random. We conclude that a random environment imposes permanent loss of correlations to the system

Neste trabalho, apresentamos uma introdução à teoria da informação quântica. Antes de lidarmos com a informação quântica propriamente dita, desenvolvemos alguns assuntos preliminares, a teoria clássica da informação e conceitos relevantes em dinâmica de sistemas quânticos. Depois, de?nimos medidas de correlações quânticas, concorrência e discórdia quântica, e estudamos sua evolução dinâmica quando o acoplamento do sistema com o ambiente é modelado como aleatório. Concluímos que um ambiente aleatório impõe uma perda permanente nas correlações do sistema
Keywords: Teoria quântica; Sistemas abertos (Física); Informação quântica; Estados coerentes